2021
DOI: 10.3389/fmolb.2021.624575
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Radiotherapy-Associated Genes in Lung Adenocarcinoma by an Integrated Bioinformatics Analysis Approach

Abstract: Radiotherapy (RT) plays an important role in the prognosis of lung adenocarcinoma (LUAD) patients, but the radioresistance (RR) of LUAD is still a challenge that needs to be overcome. The current study aimed to investigate LUAD patients with RR to illuminate the underlying mechanisms. We utilized gene set variation analysis (GSVA) and The Cancer Immunome Atlas (TCIA) database to characterize the differences in biological functions and neoantigen-coding genes between RR and radiosensitive (RS) patients. Weighte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 59 publications
(62 reference statements)
0
8
0
Order By: Relevance
“…To date, in the field of tumor biology, only a few studies revealed that IFI35 promoted the radiosensitivity of lung adenocarcinoma and colorectal cancer ( 21 , 22 ). Herein, we explored the positive correlation between IFI35 expression and M1 infiltration in TNBC from bioinformatics analysis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To date, in the field of tumor biology, only a few studies revealed that IFI35 promoted the radiosensitivity of lung adenocarcinoma and colorectal cancer ( 21 , 22 ). Herein, we explored the positive correlation between IFI35 expression and M1 infiltration in TNBC from bioinformatics analysis.…”
Section: Discussionmentioning
confidence: 99%
“…IFI35 knockout mice and IFI35 neutralizing antibodies reduce inflammation-related lung injury ( 20 ). However, there are still very few studies on IFI35 in tumor biology, among which mainly focused on enhanced radiosensitivity of lung adenocarcinoma and colorectal cancer ( 21 , 22 ). Thus, exploration for the relationship between IFI35 and macrophages polarization is an attractive direction for cancer immunotherapy.…”
Section: Introductionmentioning
confidence: 99%
“…Human Cell Landscape ( http://bis.zju.edu.cn/HCL/ ) [ 20 ] and PanglaoDB ( https://panglaodb.se/index.html ) [ 21 ] databases were used to analyze the cell types of human embryos and adults, and the expression levels of CD276 in various types of tissue. The expression levels of CD276 in adult and fetal brain tissues, and different cell types therein, were analyzed.…”
Section: Methodsmentioning
confidence: 99%
“…TISIDB ( http://cis.hku.hk/TISIDB ) is a publicly available web portal that includes a summary of 988 immune-related antitumour genes for 30 cancer types from the TCGA ( Ru et al, 2019 ; Wang et al, 2021 ). TISIDB provides a tool to analyse the interaction of certain genes with lymphocytes, immunomodulators and chemokines.…”
Section: Methodsmentioning
confidence: 99%